Semiclassical methods in molecular scattering and spectroscopy : proceedings of the NATO ASI Cambridge, England, 1979 - Child, M. S.; NATO ASI (1979 : Cambridge, England) (Dordrecht, Holand : D Reidel Pub., 1980)
42